Nano-herb medicine and PDT induced synergistic immunotherapy for colon cancer treatment. (February 2021) - Wu, Xiaoli; Yang, Han; Chen, Xingmeng; Gao, Junxiao; Duan, Yue; Wei, Daohe; Zhang, Jinchao; Ge, Kun; Liang, Xing-Jie; Huang, Yuanyu; Feng, Sizhou; Zhang, Rongli; et al.
Abstract: A variety of therapies have been developed and used for the treatment of colon cancer, however, the high mortality rate remains high and more effective strategies are still in urgent needs. In this study, an immunotherapy approach that is composed of innate immune activator Astragaloside III (As) and the photodynamic therapy (PDT) reagent chlorine e6 (Ce6) ((As + Ce6)@MSNs-PEG), was developed for colon cancer treatment. We showed that (As + Ce6)@MSNs-PEG could effectively activate NK cells and inhibit the proliferation of tumor cells in vitro . It could also effectively reach tumor sites, induce infiltration of immune cells into the tumor, and enhance the cytotoxicity of natural killer cells and CD8 + T cells in vivo . Without obvious side effects, (As + Ce6)@MSNs-PEG treatment significantly inhibited tumor growth and extended the lifespan of tumor-bearing mice. Further results revealed that treatment of (As + Ce6)@MSNs-PEG led to enhanced IFN secretion by immune cells and increased T-box transcription factor (T-bet), which is highly expressed by T cells. Therefore, (As + Ce6)@MSNs-PEG may serve as an effective and safe platform for combinatory use with nano-herb medicine and PDT to provide a new therapy for colon cancer treatment.